Oropharyngeal cancer: an emergent disease? - Martín Granados-García (Instituto Nacional de Salud Pública, 2016)
Oropharyngeal cancer incidence has recently increased, thereby attracting public attention. Akin to other malignancies of the upper aerodigestive tract, it has been attributed to the carcinogenic effects of tobacco and alcohol use. However, recent evidence shows that a substantial increase in the disease is attributable to the effects of human papillomavirus (HPV). Marked progress has been made in relation to the knowledge of molecular and genetic mechanisms involved in the genesis and progression of these cancers. This has led to the development of new and promising therapies of a more specific and less toxic nature that have prolonged life and improved its quality. However, these therapies have failed to significantly increase the proportion of patients who are cured. To decrease the mortality associated with these neoplasms, it is necessary to adopt public health measures aimed at prevention and early diagnosis.   DOI: http://dx.doi.org/10.21149/spm.v58i2.7798